Math CentralQuandaries & Queries


Question from Paulo, a student:

converting y=mx+b into ax+by+c=0 and vice versa


To convert from y = mx+b to ax+by+c = 0 we only have to move everything to one side by subtracting terms.
Ex/ y = 3x+2 converts to y-3x-2 = 0
(We subtracted 3x and 2 from both sides of the equation)

To convert from ax+by+c = 0 to y = mx+b we need only to solve for y.
Ex/ 4x+2y-6 = 0 converts to 2y = -4x+6
then dividing by 2 gives y = -2x+3


About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS